Las políticas de acción afirmativa en la gestión pública: caso sector indígena del cantón Pujilí. - Balcazar Pérez, Erika Jeanine (2024)
The research focuses on the "Equitable Access Policy to Public Services for Indigenous Communities in the Pujilí Canton" and its main objective is to examine the public policies of affirmative action in public management for the indigenous sector of this canton in the province of Cotopaxi, Ecuador. The central problem that this research addresses is to identify and understand the affirmative action strategies that are implemented within public policies aimed at strengthening the indigenous sector in Pujilí. The indigenous communities of Pujilí have historically faced significant challenges in accessing quality public services, including education, health, housing and employment. Public policy is conceived as a key tool to correct these disparities and promote equity in access to essential services. The study is based on an extensive literature review and data collection through surveys and documentary analysis. Current public policies, their scope and effectiveness are analyzed. In this sense, the main results show that in terms of knowledge about public policies, the age group of 31 to 45 years shows the highest rate of negative responses (62.8%). That same group also shows the highest number of negative responses regarding applicability (40.7%). Meanwhile, with respect to the impact, the group between 18 and 30 years old has the highest average of negative responses with 44%. The results of this research will provide a comprehensive view of public affirmative action policies in the Pujilí canton, allowing authorities, indigenous organizations and civil society to better understand the approaches that have been used and evaluate their impact.